Absorption cross sections of n-butane, n-pentane, cyclopentane and cyclohexane. (November 2022) - Sorensen, Jason J.; Bernath, Peter F.; Johnson, Ryan M.; Dodangodage, Randika; Cameron, W. Doug; LaBelle, Keith
Highlights: High resolution infrared Fourier transform spectroscopy. Absorption cross sections of n-butane, n-pentane, cyclopentane and cyclohexane. For remote sensing in planetary atmospheres. Abstract: The infrared absorption cross sections of pure n -butane, n -pentane, cyclopentane and cyclohexane have been measured in the 3.3 µm region (and 6.8 µm region for cyclopentane) by high resolution Fourier transform spectroscopy. The samples had temperatures of 294 K and 230 K for n -butane, 294 K and 218 K for n -pentane, 296 K and 235 K for cyclopentane, and 294 K and 222 K for cyclohexane. These spectra are important for molecular identification in extraterrestrial environments such as Saturn's moon Titan, giant planets and exoplanets. All spectra are provided as data point files.